Inducción de Rhizobium japonicum en la masa fermentativa de dos variedades de cacao (Theobroma cacao L.) nacional y trinitario como estrategia para la disminución de cadmio. - Vásquez Cortez, Luis Humberto (2021)
Chocolate consumption at national and international level has a very high rate. To be exported must comply with Regulation 488/2014 of the European Union. The main goal of this research was to determine whether with Rhizobium japonicum application in fermentation there is a reduction of cadmium in cocoa almonds; and, if their sensory conditions or aspects would improve with the induction of the microorganism that was induced once harvested and applied to fresh cocoa, at different concentrations 3%(60 ml) and 5%(100 ml), during the fermentation time physical analyses were carried out to know its pH, Brix and temperature. Almonds were dried in the sun for 6 days, after this they were tested for fermentation status. For every hundred random almonds a sensory analysis was performed on cocoa paste where aroma, flavor, acidity, bitterness and intensity were evaluated; with the help of a semi-trained tasting panel of ten people, the above-mentioned variables were sensory-known with significant results; in addition, a cost-per-treatment analysis was performed to determine profitability based on the induction of this microorganism resulting in witnesses T1 and T4 ($52.02) and other inductions T2,T3,T5,T6 with an average of ($53.94) giving as an average difference of 1.92 ctvs. It was fixed to know how much cadmium decreased with the application of Rhizobium japonicum for which the same data was sent to the WSS laboratory with really acceptable results. Keywords: Rhizobium japonicum, cocoa, analysis, cadmium, sensory, concentrations, induction, treatments.